The Influence of Check-In Counter Officer Service Quality on Passenger Satisfaction at Transnusa Airlines at Soekarno-Hatta International Airport - Negara, M. Ryan Prawira; Yosepha, Sri Yanthy (Dinasti Publisher, 2025)
Passenger satisfaction is important in maintaining loyalty and airline reputation in the aviation industry. One important aspect of airline service quality is the check-in counter officer. Check-in counter officers are the front line in direct interaction between airlines and passengers. This study analyses the service quality of check-in counter officers and their effect on passenger satisfaction at Transnusa Airlines at Soekarno-Hatta International Airport. This study uses a descriptive method with a quantitative approach. The primary data was collected from processing questionnaire data from 100 respondents using the accidental sampling method. The study's results found that the quality of check-in officer service observed through the variables reliability, responsiveness, assurance, empathy, and tangible proved to have a significant effect both partially and simultaneously on TransNusa airline passenger satisfaction. The assurance variable is the variable that has the most dominant influence on passenger satisfaction. The magnitude of the contribution of the influence of service quality (reliability, responsiveness, assurance, empathy and physical evidence) on TransNusa airline passenger satisfaction is 86.1%.